Christian spirituality an historical sketch - Lane, George A., 1934- (Chicago, IL Loyola University Pr, 1984)
Includes bibliographical references.
Originally presented as lectures by Thomas M. Gannon, George W. Traub, & George A. Lane.
Keywords: Spirituality -- Catholic Church -- history; Catholic Church -- doctrines